Inter-individual responses to acute resistance training in the blood pressure dipping response in normotensive and hypertensive men - Carpio Rivera, Elizabeth (2024)
The blood pressure dipping response to acute resistance training exercise (RTE) is scarce in the literature. We determined the inter-individual blood pressure (BP) dipping variability of normotensive (NT) and hypertensive (HT) men completing two modalities of a single session of RTE. Volunteers (NT n = 21, HT n = 20) underwent a non-exercise control (CTRL), RTE high-sets low-repetitions (HSLR), and RTE high-repetitions low-sets (HRLS) conditions. Twenty-four-hour ambulatory BP monitoring recorded diurnal and nocturnal systolic (SBP) and diastolic (DBP) BP. Non-significant interactions were found between the category of individuals and the experimental conditions on the SBP (p = 0.511, η²ₚ = 0.02) and DBP (p = 0.807, η²ₚ = 0.01) differences. Diurnal SBP (p = 0.0001) and DBP (p ≤ 0.0001) were lower in the NT than in the HT groups. Nocturnal SBP (p ≤ 0.0001) and DBP (p = 0.014) were lower in the NT than in the HT groups. The percentage of dipping responders for SBP in the CTRL condition were 71.4% for NT and 70.0% for HT, in the HRLS condition were 66.7% for NT and 60.0% for HT, and in the HSLR condition were 57.1% for NT and 60.0% for HT. The dipping responders for DBP in the CTRL condition were 57.1% for NT and 60.0% for HT, in the HRLS condition were 61.9% for NT and 70.0% for HT, and in the HSLR condition were 71.4% for NT and 65.0% for HT (p > 0.05 for all). In conclusion, the dipping response was similar between NT and HT individuals. The proportion of responders was similar between NT and HT individuals completing acute RTE.